Safety and Immunogenicity of Monovalent Omicron KP.2-Adapted BNT162b2 COVID-19 Vaccine in Adults: Single-Arm Substudy from a Phase 2/3 Trial - Oyeniyi Diya; Juleen Gayed; Francine S. Lowry; Hua Ma; Vishva Bangad; Federico Mensa; Jing Zou; Xuping Xie; Yanping Hu; Mark Cutler; Todd Belanger; David Cooper; et al. (Infectious Diseases and Therapy)
Abstract Introduction COVID-19 continues to cause substantial health burden, particularly among vulnerable populations. Vaccines remain a vital tool in preventing severe disease outcomes. As the causative pathogen, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to evolve; therefore, updates may be needed to closely match COVID-19 vaccine composition to predominant circulating lineages to confer optimal protection. Methods In this cohort from a substudy of an ongoing phase 2/3 trial, 102 healthy adults (18‒55 and > 55 years of age, n = 51 each) were vaccinated with Omicron KP.2-adapted BNT162b2. Serum neutralizing titers against Omicron KP.2, JN.1, and KP.3 were assessed before and through 1 month after vaccination. Immunogenicity in KP.2-adapted BNT162b2 recipients was compared with participants who received JN.1-adapted BNT162b2 in an earlier cohort of this substudy. Local reactions and systemic events through 7 days and adverse events (AEs) through 1 month are reported. Results One month after vaccination, KP.2-adapted BNT162b2-elicited neutralizing titers against Omicron KP.2, JN.1, and KP.3 were numerically higher than those induced by JN.1-adapted BNT162b2. Geometric mean fold rises from before to 1 month after vaccination were numerically higher in those who received KP.2-adapted BNT162b2 compared with those who received JN.1-adapted BNT162b2 (9.4 vs. 6.8 for KP.2; 7.8 vs. 5.7 for JN.1; 9.2 vs. 7.0 for KP.3). Percentages of participants with seroresponses were numerically higher against KP.2 after KP.2-adapted BNT162b2 than JN.1-adapted BNT162b2 (75% vs. 65%) and similar against JN.1 and KP.3 for both vaccines (69% vs. 67% for JN.1; 74% vs. 73% for KP.3). Local reactions and systemic events were all mild to moderate in severity, AEs were infrequent, and no serious AEs or AEs leading to withdrawal were reported. Conclusions Collectively, these immunogenicity, safety, and tolerability data support administration of KP.2-adapted BNT162b2 to protect against contemporaneous circulating lineages. ClinicalTrials.gov Identifier NCT05997290.